ALBANIAN HOTELS AND SUSTAINABLE TOURISM PRACTICES - Gaspari, Alda (European Scientific Journal, ESJ, 2015)
The tourism industry is growing rapidly and the loss of natural landscapes, local identities and traditional cultures; degradation of the environment are often listed as negative impacts associated with the tourism industry’s development . The accomodation sector has been described as part of the industry , which activities cause negative impact on the environment,calling urgently for greater participation in sustainable tourism practices . Previous studies indicate that SMTEs, often focus on business returns by employing unsustainable business practices .To minimise any negative impacts that may arise as the result of tourism activities, efforts are now geared towards alternative form of tourism (Butler, 1993),which most academic literatures describes as ‘sustainable tourism’ (Edwards, 2004; Bohdanowicz, 2005). The research objective of the study in this paper is to explore and discuss the concept of sustainable practices within the tourism industry . The paper moves on to look at albanian tourism enterprises which develop their activity in Korca,Vlora,Saranda,Durres,Pogradec cities , their current level of participating in sustainable tourism practices in daily routine operations. As conclusion, findings of this study revealed hotels commitment to different sustainable practices varies to some extent and certain practices are unpopular to them . To have a tourism which relies heavily on sustainability ,a massive involvement in these practices should be undertaken